2007
DOI: 10.1007/s10461-007-9333-5
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use, Intimate Partner Violence, Sexual Coercion and HIV among Women Aged 15–24 in Rakai, Uganda

Abstract: Disinhibition due to alcohol may induce intimate partner violence and sexual coercion and increased risk of HIV infection. In a sample of 3,422 women aged 15-24 from the Rakai cohort, Uganda, we examined the association between self-reported alcohol use before sex, physical violence/sexual coercion in the past and prevalent HIV, using adjusted odds ratios (Adj OR) and 95% confidence intervals (95% CI). During the previous year, physical violence (26.9%) and sexual coercion (13.4%) were common, and alcohol use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
149
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(163 citation statements)
references
References 34 publications
12
149
2
Order By: Relevance
“…An additional eight nonoverlapping studies published prior to 2009 were identified from our previous narrative review (Allen et al, 1992;Bassett et al, 1996;Clift et al, 2003;Dunkle et al, 2004;Fisher, Cook, Sam, & Kapiga, 2008;Msuya et al, 2006;St. Lawrence et al, 2006;Zablotska et al, 2009) and three additional studies reported in Pithy and Parry (2009) (Mitsunaga & Larsen, 2008;Mmbaga et al, 2007;Seme, Mariam, & Worku, 2005). These additional three studies were likely not included in our review due to the use of different electronic databases (PsycINFO vs. PubMed).…”
Section: Methods Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional eight nonoverlapping studies published prior to 2009 were identified from our previous narrative review (Allen et al, 1992;Bassett et al, 1996;Clift et al, 2003;Dunkle et al, 2004;Fisher, Cook, Sam, & Kapiga, 2008;Msuya et al, 2006;St. Lawrence et al, 2006;Zablotska et al, 2009) and three additional studies reported in Pithy and Parry (2009) (Mitsunaga & Larsen, 2008;Mmbaga et al, 2007;Seme, Mariam, & Worku, 2005). These additional three studies were likely not included in our review due to the use of different electronic databases (PsycINFO vs. PubMed).…”
Section: Methods Literature Reviewmentioning
confidence: 99%
“…There were a few notable exceptions: (1) Ayisi et al (2000) reported adjusted and unadjusted risk ratios, (2) Talbot et al (2002) reported adjusted and unadjusted prevalence ORs, and (3) all but two of the cohort studies (Allen et al, 1992;Kalichman et al, 2010) provided rate ratios or data for calculation of a rate ratio (Kapiga et al, 1998;Shaffer et al, 2010;Zablotska et al, 2006Zablotska et al, , 2009. In these instances, the measure of association reported by the authors was used in order to retain the benefit of adjusted rate/risk ratios, although separate analyses were conducted based on study design (e.g., case-control vs. cohort studies).…”
Section: Data Abstractionmentioning
confidence: 99%
“…One of these studies examined the association between alcohol use before sex (by at least one partner) and lifetime sexual coercion with prevalent HIV among young women (aged 15 -24 years). The authors found that alcohol use before sex, and especially prior sexual coercion and alcohol use before sex, was significantly associated with prevalent HIV (Zablotska et al, 2009). In the other study the use of alcohol before sex was significantly associated with an increased risk of HIV acquisition among both women and men (Zablotska et al, 2006).…”
Section: Original Articlementioning
confidence: 99%
“…In another study using data from the same community-based survey, Mitsunaga and Larsen (2008) The association between self-reported alcohol use before sex, physical violence/sexual coercion in the past and HIV prevalence was examined in a sample of young women from a population-based cohort in Rakai, Uganda (Zablotska et al, 2009 …”
Section: Community/population-based Studiesmentioning
confidence: 99%
“…Features and behaviours of a male partner that increase a woman's likelihood of experiencing IPV are the male being under 25-years-old (Stats Can, 2005), his use of substances Foran & O'Leary, 2008;Golinelli, Longshore, & Wenzel, 2008;Hazen & Soriano, 2007;Muhajarine & D'Arcy, 1999;Stalans & Ritchie, 2008;Stats Can, 2005;Vatnar & Bjorkly, 2008;Zablotska et al, 2007), his use of emotional and psychological abuse (Stats Can, 2005), exertion of power and control over his partner (Fox et al, 2007;Sonis & Langer, 2008), and having more than one sexual relationship at a time (Fox et al, 2007).…”
Section: Prevalence Of Ipv For Womenmentioning
confidence: 99%